An investigation into the proficiency of successful late learners of French - Kinsella, Ciara (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2009)
The introduction to tiiis thesis provides a background for the study as well as the reasons behind the choice of subject. In the second chapter of the thesis there is a review of the literature on the Critical Period Hypothesis and first and second language acquisition. The literature is examined and some shortfalls are pointed out. Studies conducted on near-native speakers are detailed and analysed as well as providing a context for this present study.
Keywords: Applied Linguistics, Ph.D.; Ph.D. Trinity College Dublin